Empirical investigation on the barriers of adoption of cryptocurrency-based transaction from an Islamic perspective - Al-Hussaini, Abulfathi Ibrahim Saleh; Noordin, Mohamad Fauzan; Abubakar, Adamu; Mohd Mohadis, Hazwani
Purpose: This paper presents a user study of “perception of the cryptocurrency-based transaction from the Islamic views”. Bitcoin is considered the special type of cryptocurrency used in this study. Users view bitcoin is as an app that provides a personal currency in a digital wallet through which transactions can occur in order to either send, receive, buy, or sell the currency (bitcoins). Information System is an enabler of this mode of transaction, unfortunately, some users raised concern about the nature of transactions with Bitcoin. Specifically, some argued that Bitcoin can be easily used for illegal purposes and that the global public already uses Bitcoin mostly for illegal and Shari’ah non-compliant purposes under Islamic views. Design/methodology/approach: This study adopted “Technological Acceptance Model” and utilized quantitative research methodology, in order to formulate and test some hypotheses that will lead to an establishment of a model. A sample of 306 participants was used in the study. Findings: The result of the hypothesis testing indicate that “Behavioral Intention to Use Cryptocurrency from the Islamic perspective” is influenced directly by Shari’ah Compliance, Perceived Ease of Use, Emotionality, Perceived Usefulness, and Financial Concern. As evident from the analysis, Emotionality is influenced directly by Financial concern and Shari’ah Compliance. Whereas, Behavioral Intention is influenced indirectly by Financial Concerns. Research limitations/implications: The sample is general and does not specify a specific group of study. Practical implications: This study has contributed to understanding the Islamic issues behind the implementation of Cryptocurrency Originality/value: The study formulates and tests a theory for cryptocurrency-based transaction from an Islamic view.